Pengaruh Sisa Lebih Perhitungan Anggaran, Fiscal Stress dan Pendapatan Asli Daerah terhadap Penyerapan Anggaran dengan Rebudgeting sebagai Variabel Moderasi - Silvia Wulandari; Eka Fauzihardani (Jurnal Eksplorasi Akuntansi, 2022)
This research aimed to analyze remaining budget calculations, fiscal stress, local revenue on budget absorption with rebudgeting as moderating variables in regency/city governments in West Java Province. The population in this study were all 27 regency/cities in West Java Province. The sample collection method used purposive sampling, while the data processing method used multiple linear regression analysis. The results of statistical tests show that the remaining excess of budget calculations and local revenue has a significant positive effect on budget absorption, but fiscal stress has no effect on budget absorption. rebudgeting as a moderating variable can moderate the relationship between the remaining excess of budget calculations and budget absorption but rebudgeting is not able to moderate the relationship between fiscal stress, local revenue and budget absorption.